Guiding principles of good tax policy: Is there an association between the principles of the income tax of Nepal and the principles of good tax policy suggested by AICPA? - K.C., Jit Bahadur (Pravaha, 2020)
Purpose – This article aims to examine the association between principles of income tax in Nepal and the principles of good tax policy prescribed by AICPA. Materials and methods – This study uses both primary and secondary data. Forth primary data, the study obtained data from several individuals using the Likert type scale questionnaires. To obtain the answer upon research questions and to reach into the conclusion, the study used the Chi-square and summated rating scale. Findings – The study found an association between the principles of income tax in Nepal and the guiding principles of the good tax policy suggested by AICPA. Only on three principles (i.e., certainty, information security and economic growth and efficiency) out of the twelve guiding principles came into the acceptance ofH0 (null hypothesis) while others came into the acceptance of H1 (alternative hypothesis). However, the study concludes that Nepal needs reform/s to its income tax principles to make them compatible with the principles of other countries. Practical implications – Theory and practice both are complementary to each other. Every theory is worthless in the absence of practice and vice versa. The theory, which people perceive as simple, progressive, and democratic is fundamental and practical. Thus, this writing keeps crucial importance in the government revenue sector and suggests being practical after reforming the required policy. Originality/value – This is survey research to find out the association between the principles of income taxation in Nepal and the guiding principles of good tax policy suggested by the AICPA. For which, the author prepared this product using both primary and secondary sources of data based on Kathmandu valley. Thus, this is original writing in this subject.